How sustainable is the gain in food consumption of the CFPR/TUP beneficiaries? - Haseen, Farhana; Sulaiman, Munshi (BRAC Research and Evaluation Division and Aga Khan Foundation Canada, 2022)
Despite some remarkable improvements in nutritional status, malnutrition in Bangladesh is still highly prevalent, especially among the poorest. A number of initiatives are taking place that address the food intake of the ultra-poor, either directly or indirectly. Challenging the Frontiers of Poverty Reduction/ Targeting the Ultra Poor (CFPR/TUP) has become the key program for BRAC to help the most disadvantaged population. To provide a clear pathway of graduation to the beneficiaries after two years of intensive supports, this program was launched in 2002 in three northern districts of Bangladesh. Three rounds of surveys were conducted – prior to intervention (in 2002), after two years of intervention (in 2004), and two years after the termination of active intervention (in 2006)—to assess whether CFPR/TUP intervention can secure a sustainable impact on food consumption of the beneficiaries. Food and calorie consumption among the beneficiary households increased significantly between 2002 and 2004 (during intervention) and the upward trend continued in 2006. Mean intakes of protein, fat, carbohydrate, calcium, iron, vitamin C, and retinol were higher in beneficiaries compared to non-beneficiaries both in 2004 and in 2006. Improvements were observed both in quantity and quality of food intake. Beneficiary households had a more diversified diet with a significant amount of animal source foods and spent more on food consumption.